Pathogens Causing Bacteraemia in Tertiary Care Hospital in India: Microbiological Diagnosis and Antimicrobial Sensitivity Pattern - C. Jegan; V. Mangayarkarasi; A. R. Rukadikar; V. Anandi (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The present study was thus undertaken to know the prevalence of pathogens causing bacteremia along with antibiotic sensitivity pattern in a tertiary care setting to guide clinicians to initiate empiric antibiotic therapy and to formulate antibiotic policy. Hospital based prospective cross sectional study conducted at SRM Medical College Hospital and Research Centre, Potheri, Kanchipuram District, Tamil Nadu, India, during March 2012 to February 2013. The prevalence of bacteremia, the common causative organisms causing this infection and its antibiotic resistant pattern, the morbidity and mortality in a rural population are under reported in most of the developing countries including India. Study shows the prevalence of bacteremia was 14.90% among 765 patients of all age groups. such studies will aid in developing management guidelines and antibiotic policy for better outcome of the patients with bacteremia.